Meningkatkan Akuntabilitas Pengelolaan Pendapatan Daerah melalui Integrasi Pengawasan Internal, Kompetensi SDM, dan Sistem Informasi (Studi pada Dinas Pendapatan Kabupaten Buleleng) - Wenas Yohanes Berchmans; Komang Krisna Heryanda; M.Rudi Irwansyah (KRISNA: Kumpulan Riset Akuntansi, 2026)
Accountability in regional revenue management is a fundamental element in achieving transparent and responsible public governance. Low levels of accountability in revenue management may reduce public trust in local government performance. This study aims to examine the influence of internal control, human resource competence, and information systems on the accountability of regional revenue management at the Regional Revenue Office of Buleleng Regency. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 40 employees involved in regional revenue management. The collected data were analyzed using multiple linear regression analysis with statistical software. The results indicate that internal control and human resource competence have a positive and significant effect on the accountability of regional revenue management. Meanwhile, information systems show a relatively smaller effect, although they still contribute to improving accountability. These findings suggest that strengthening internal control mechanisms and enhancing employee competence are key factors in improving the accountability of regional revenue management. This study provides practical implications for local governments in improving revenue management through strengthening internal control systems, developing employee competencies, and optimizing the use of information systems.